ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI PADA SIKLUS PENDAPATAN GUNA MENINGKATKAN PENGENDALIAN INTERNAL PERUSAHAAN YANG MENJUAL KOMPONEN SEPEDA MOTOR - LEONARDO AGUSTANTO, HENDRA (Berkala Ilmiah Mahasiswa Akuntansi)
This study uses a case study on the CV X which is a company engaged in the sale of motorcycle spare parts. Manual accounting information system that now requires a long time for the reporting process and the results are less accurate. The purpose of this research is to design a repair system of accounting information on revenue cycle CV X, in order to increase the company's internal control. The type of data in this study using qualitative data and data sources used to use secondary data. The data in this thesis comes from the company obtained through interviews, observation, and documentation. Instruments used to collect data on the study include tape recorders, records, and interview guides. Data analysis techniques to analyze the problem of companies using SAS 94, perform the conceptual design of a HIPO, DFD, ERD, flowcharts, as well as interfaces. At the stage of physical design, output, database, inputs, and control inputs are designed. From design output, generated sales reports by date, goods, and customers, reports the details of receivables per customer, ordering statements and statements of cash receipts. From the database design, produced tables or databases of customers, items, sales, invoicing, SJ, cash receipts, returns. From the design of the input generated sales order form, mail path, invoices, and cash receipts.